Waukesha County library system public opinion survey - Trechter, David; Hadley, Shelly; Parks, Denise (My University, 2008)
The goal of the Waukesha County Library System (WCLS) survey was to determine average library usage, opinions about the value of the WCLS, and economic considerations associated with the library. A key question to be addressed by this survey was to determine if people living in jurisdictions that don't currently have a library branch use them differently and have different opinions about them.
53 p.
Keywords: Waukesha County libraries; Waukesha County, Wisconsin; Waukesha County (Wis.); Waukesha County Library System; Library surveys--Wisconsin--Waukesha County; Public libraries--Wisconsin--Waukesha County--Public opinion; Public libraries--Wisconsin--Waukesha County--Evaluation